Optimization of Melt and Coolant Temperature on Defects of Injection Molded Toothbrush Handle - Mochammad Arief Susetyo; Andoko Andoko; Yanuar Rohmat Aji Pradana (TRANSMISI, 2023)
The toothbrush handle is an injection molded product that rejects up to 10%. One of the factors that cause defects is the injection molding process settings, namely melting and cooling temperature. The purpose of this optimization is to obtain the optimum value of melt and cooling temperature parameters on product quality (minimum defects) of toothbrush handles using RSM. The methods used include simulation using ANSYS to obtain mold temperature, Autodesk Moldflow to obtain product defects and quality prediction based on input parameters of melt temperature (190o , 200o , and 210o C) and coolant temperature (22o , 24o , and 26o C), and Minitab 19 for RSM optimization. The simulation results that cooling temperature and melt temperature that are too low and high result in high defect values (weld line and shrinkage) in the product, resulting in low quality prediction values. Based on the results of the optimized simulation, the best injection molding setting is at a melt temperature of 200oC and a cooling temperature of 24oC which obtains a toothbrush handle product quality response variable of 78.04% with a minimum weld line value of 0.0277o and a minimum shrinkage depth of 0.009 mm.